Comparison of Hepcidin Levels in Children with and without Soil-Transmitted Helminths Infection - Dewi Saputri; Yunilda Andriyani; Almaycano Ginting (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Helminths infection is one of the diseases that still occur insociety. The helminth infection caused by theSoil-Transmitted Helminths (STHs) group, which is Ascaris lumbricoides, Trichuris trichiura, and hookworm in human cancause chronic bleeding resulting in decreasir on storage in the body and increased level of hepcidin. Hepcidin is a liverhormone which regulates iron metabolism and can function as marker of inflammation and iron deficiency. This study aimedto compare the hepcidin levels in STH-infected and non-infected children. A cross-sectional study was conducted betweenMay and October 2018 on 28 STH infected and 140 non-infected subjects. The collected stool samples were analyzed usingthe Kato-Katz method to determine the presence of STH infection and the degree of infection. Urine samples wereprocessed, and their hepcidin levels were measured using a Sandwich-ELISA method. Measurement was made using aSpectrophotometer. The difference of numeric variables was analyzed using Wilcoxon test. The prevalence of STH infectionwas 16.66%. The prevalence of Trichuris trichiura 10.71%, Ascaris lumbricoides 4.76% and hookworm 2.97%. The prevalenceof a single infection was 14.88% and mixed infection 1.78%. Based on the intensity of infection, 15.48% of subjects were mildinfection, 0.59% moderate infection, and 0.59% severe infection. Hepcidin levels in the infected and uninfected group didnot differ significantly (p=0.978). There were no different hepcidin levels in children with and without soil-transmittedhelminths infection.